Table of Content - - (Journal of Economic, Administrative and Legal Sciences, 2025)
Table of Content: 1. Marketing policies and their impact on attracting new customers (applied to Sin Flour Mills Company, Atbara), Sudan Asst-Prof. Mohamed Ibrahim Mohamed Ali 2. Beneficiaries’ Satisfaction with the Quality of Health Services: A case Study of Al-Salam University Hospital, River Nile State, Sudan Dr. Yousif Awad-Elkarim Abu Elhassan ,Dr. Mohi-Eldin Ali Mohi-Eldin,Dr. Osman Abdalla Mohamed Elhadi, Dr. Eslam Hassan Gorshi 3. Impact of Training Courses on Skill Development and Performance Enhancement of Private Sector Employees in the Eastern Region of Saudi Arabia Ms. Fatima Ahmed Mohammed Bin Huwaishil 4. Analysis of the impact of artificial intelligence technologies on reducing costs and increasing the efficiency of resource use in technology development projects in The Kingdom of Saudi Arabia Dr. Anwar Mohammed Qism-Allah Mohammed 5. Trends in the Adoption of Artificial Intelligence in Knowledge Management: An Analytical Study Using the Technology Acceptance Model (TAM) in Saudi Organizations in Line with Vision 2030 Ms. Asmaa Yahia Saeede 6. The role of the knowledge economy in human development in Sudan during the period from 1992 to 2022 Co-Prof. Mohamed Abdalla Mohamed Ahmed 7. The Role of Artificial Intelligence in Improving the Efficiency of Financial and Accounting Performance: A Field Study on some Sudanese business organizations Asst-Prof. Suleiman Musa Elzain Hammad